Alterações em marcadores do estresse oxidativo ocasionadas por diferentes tempos de tratamento com chá mate (Ilex paraguariensis) no processo de envelhecimento - Tirapeli, Keny Gonçalves [UNESP] (2014)
Erythrocytes have been used to investigate oxidative damage and possible intervention with antioxidant in aging. Mate tea (MT) or Ilex paraguariensis reduces oxidative damage, but its action on aged females has not yet been elucidated. It was investigate, for the first time, in natural aged rats in perimenopause the time-dependent effect of MT treatment on oxidative damage and antioxidant defenses. Animals were divided into Adult-control (5 months old), Aged-baseline, Aged treated and Aged untreated. Treated groups received MT daily (20 mg/kg body weight, gavage) for two, four or six weeks, aged untreated group received water by gavage. Plasma antioxidant capacity, determined by ferric reducing antioxidant power (FRAP) assay, malondialdehyde levels (MDA) and the activities of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) enzymes were evaluated in erythrocytes. Aged-baseline animals (17 months) had decreased FRAP and enzymatic antioxidant defenses and increased MDA when compared to Adult-control (5 months). MT treatment increased FRAP, SOD, GPx, and decreased MDA after four weeks, but did not change CAT. MT is a promising treatment to reduce the accumulation of age-related oxidative damage in erythrocytes in aged rats in perimenopause and the effect is cumulative in FRAP